Roman republics - Flower, Harriet I. (Princeton University Press, 2010)
From the Renaissance to today, the idea that the Roman Republic lasted more than 450 years--persisting unbroken from the late sixth century to the mid-first century BC--has profoundly shaped how Roman history is understood, how the ultimate failure of Roman republicanism is explained, and how republicanism itself is defined. In Roman Republics, Harriet Flower argues for a completely new interpretation of republican chronology. Radically challenging the traditional picture of a single monolithic republic, she argues that there were multiple republics, each with its own clearly distinguishable s.